(untitled) (The Review of Diabetic Studies, 2024)
General health is a fundamental determinant of population well-being and social development, determined by biological, behavioral, and communal factors. Strengthening general health depends on effective health systems supported by a competent and resilient health workforce. This article analyzes the role of health care professionals in progressing general health through disease prevention, health promotion, clinical care, and multidisciplinary collaboration. It outlines the contributions of physicians, nurses, pharmacists, allied health professionals, and public health practitioners in meeting both individual and population-level health needs. The discussion also addresses challenges experienced by health care professionals, including workforce shortages, burnout, and increased demands on health systems. Recognizing and supporting the contributions of health care professionals is important for preserving strong health systems as well as enhancing health outcomes. Investment in the health workforce is still a critical element of strategies to improve overall health.